Voice-only communication enhances empathic accuracy - Kraus, Michael W (The American psychologist, 2017)
This research tests the prediction that voice-only communication increases empathic accuracy over communication across senses. We theorized that people often intentionally communicate their feelings and internal states through the voice, and as such, voice-only communication allows perceivers to focus their attention on the channel of communication most active and accurate in conveying emotions to others. We used 5 experiments to test this hypothesis (N = 1,772), finding that voice-only communication elicits higher rates of empathic accuracy relative to vision-only and multisense communication both while engaging in interactions and perceiving emotions in recorded interactions of strangers. Experiments 4 and 5 reveal that voice-only communication is particularly likely to enhance empathic accuracy through increasing focused attention on the linguistic and paralinguistic vocal cues that accompany speech. Overall, the studies question the primary role of the face in communication of emotion, and offer new insights for improving emotion recognition accuracy in social interactions. (PsycINFO Database Record